Legal Protection on Economic Rights of Pirated Work of Songs in Intellectual Properties - Oksidelfa Yanto; Qingqing Cindy Chen; Nani Widya Sari (Nagari Law Review, 2022)
This research aims at finding out the legal protection of copyright according to positive laws of Indonesia, and the types of legal sanctions rendered if there is an infringement on the economic rights of a songwriter. This research applies the juridical normative method to literature studies. The data which is presented in this research is secondary data. The findings show that the protection over works on songs in Indonesia has been provided by Law No. 28, 2014 concerning Copyrights. The law states that a song is one protected intellectual property. In its practice, the protection over copyright follows the automatic protection system, which means that the protection is without the process of recordation. The legal consequence is that every person who illegally commits a copyright crime, either for economic rights or for commercial use, shall face criminal sanction. Besides, the other parties other than the creator can be prohibited to exploit the creator’s economic rights. Within the sanction, other parties besides the creator are prohibited to exploit the creator’s economic rights.